Identification of Rice Genes Associated With Enhanced Cold Tolerance by Comparative Transcriptome Analysis With Two Transgenic Rice Plants Overexpressing DaCBF4 or DaCBF7, Isolated From Antarctic Flowering Plant Deschampsia antarctica - Byun, Mi Young; Cui, Li Hua; Lee, Jungeun; Park, Hyun; Lee, Andosung; Kim, Woo Taek; Lee, Hyoungseok (Frontiers in Plant Science, 2018)
Few plant species can survive in Antarctica, the harshest environment for living organisms. Deschampsia antarctica is the only natural grass species to have adapted to and colonized the maritime Antarctic. To investigate the molecular mechanism of the Antarctic adaptation of this plant, we identified and characterized D. antarctica C-repeat binding factor 4 (DaCBF4), which belongs to monocot CBF group IV. The transcript level of DaCBF4 in D. antarctica was markedly increased by cold and dehydration stress. To assess the roles of DaCBF4 in plants, we generated a DaCBF4-overexpressing transgenic rice plant (Ubi:DaCBF4) and analyzed its abiotic stress response phenotype. Ubi:DaCBF4 displayed enhanced tolerance to cold stress without growth retardation under any condition compared to wild-type plants. Because the cold-specific phenotype of Ubi:DaCBF4 was similar to that of Ubi:DaCBF7 (Byun et al., 2015), we screened for the genes responsible for the improved cold tolerance in rice by selecting differentially regulated genes in both transgenic rice lines. By comparative transcriptome analysis using RNA-seq, we identified 9 and 15 genes under normal and cold-stress conditions, respectively, as putative downstream targets of the two D. antarctica CBFs. Overall, our results suggest that Antarctic hairgrass DaCBF4 mediates the cold-stress response of transgenic rice plants by adjusting the expression levels of a set of stress-responsive genes in transgenic rice plants. Moreover, selected downstream target genes will be useful for genetic engineering to enhance the cold tolerance of cereal plants, including rice.